ExoLuminate: An observational registry study for detection of pancreatic adenocarcinoma (PDAC) in high-risk or clinically suspicious patients - Hinestrosa, Juan Pablo; Izaguirre Carbonell, Jesus; Balcer, Heath; Kurzrock, Razelle; Billings, Paul R. (Journal of clinical oncology, 2023)
TPS4203Background: The detection of pancreatic ductal adenocarcinoma (PDAC) at early-stages is critical to improving patient survival. However, the lack of a clinically useful biomarker assay poses a challenge for earlier detection. A liquid biopsy test (ExoVita Pancreas) which uses extracellular vesicles (EV) protein biomarkers has been developed for detection of PDAC. In a previous case-control study of n=715 (75 cases of PDAC Stage I and II, 640 controls), the EV-protein biomarker assay yielded a sensitivity of 96.0% and specificity of 91.1%. By optimizing the assay for high sensitivity, we aim to generate evidence for earlier detection of PDAC in high-risk and clinically suspicious patients in the hope of impacting PDAC patient diagnostic journeys. Methods: ExoLuminate is a prospective, multi-center, observational registry study to demonstrate that early detection of PDAC using ExoVita is non-inferior to current standard of care methods of surveillance. The study duration will be 36 months (24-month accrual, 12-month follow-up), with a minimum of 1000 subjects to be enrolled between two cohorts as described below. The first cohort enriches for "high-risk" individuals without a cancer suspicion or diagnosis including those with intraductal papillary mucinous neoplasms (IPMNs), personal or family history of pancreatitis, family member(s) who have at least one first-degree relative affected by pancreatic cancer, patients over 50 years of age with new-onset diabetes (NOD), and germline mutations known to be associated with PDAC. The second cohort includes patients with clinical findings suspicious for early-stage PDAC or those with biopsy-proven PDAC. Patients enrolled in the study will have their blood obtained at six-month intervals. The performance of ExoVita liquid biopsy will be compared to standard-of-care imaging and biomarkers such as CA19-9. Through this registry, which began enrollment in December 2022 and is open for accrual (NCT0562552), we aim to demonstrate the clinical utility of a novel liquid biopsy based on detection of EV-derived biomarkers for early diagnosis of PDAC which can provide credence to a new paradigm in early detection to improve patient outcomes. Clinical trial information: NCT0562552.